Programmed cell death during the formation of rhytidome and interxylary cork in roots of Astragalus membranaceus (Leguminosae). Issue 7 (17th January 2021) - Han, Xiaojing; Zhou, Yafu; Ni, Xilu; Chu, Shanshan; Cheng, Ming'en; Tan, Lingling; Zha, Liangping; Peng, Huasheng
Abstract: Programmed cell death (PCD) plays a critical role throughout the lives of plants, it is regarded as a highly regulated and active process of plant cell death during the times of biotic or abiotic stress. This study aims to provide developmental anatomical characteristics of the interxylary cork formation in the roots of Astragalus. membranaceus var. mongholicus, and to subsequently show cytomorphological evidence that PCD is involved in the development of rhytidome and interxylary cork. The developmental anatomy of rhytidome and interxylary cork of the perennial fresh main root of A. membranaceus var. mongholicus was studied using light microscopy, whereas the PCD in the development of rhytidome and interxylary cork was studied using fluorescence microscopy and transmission electron microscopy. Histologically, it was observed that the parenchyma cells of secondary phloem and xylem in roots recovered their meristematic ability, and later developed into rhytidome and interxylary cork. Cytologically, ultrastructural characteristics such as nucleus malformation, vacuole disappearance, mitochondrial degeneration, and vesicle filling were observed. In roots, the nucleus of the phloem parenchyma cells were terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end labeling (TUNEL)‐positive from the pre‐rhytidome stage to the formation of rhytidome stage and 4′, 6‐diamidino‐2‐phenylindole dihydrochloride (DAPI)‐negative during the mature rhytidome stage. The TUNEL assay of the xylem parenchyma cells showed positive characteristics from the early stage of interxylary cork formation to the interxylary cork formation stage, whereas DAPI‐negative characteristics were observed in the mature interxylary cork. Gel electrophoresis showed that DNA cleavage was random. Our results indicated that the formation of the rhytidome and interxylary cork involved the PCD process. Abstract : The roots of Astragalus membranaceus var. mongholicus contains rhytidome and a "hollow heart." In the present study, we demonstrate that the "hollow heart" is in fact an kind of interxylary cork in the secondary xylem, and the development of the ryhtidome and interxylary cork in roots of A. membranaceus var. mongholicus is related to programmed cell death (PCD). Characterization of the ultrastructure showed that DNA degradation, cytoplasmic degradation, and vesicle formation were observed in cells undergoing PCD.